2008
DOI: 10.1016/j.homp.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of homeopathically prepared thyroxine on highland frogs: influence of electromagnetic fields

Abstract: Animals treated with the standard test solution thyroxine 10(-30) metamorphosed more slowly than the control animals, ie the effect of the homeopathically prepared thyroxine was opposed to the usual physiological effect of molecular thyroxine. The cumulative number of test animals that had reached the four-legged stage at defined points in time was smaller in the group treated with homeopathically prepared thyroxine at most of the points in time. This was found independently by all three research teams involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…3 In fish it is present in form of follicles associated to the ventral aorta, it plays an important role influencing the growing of bones, cartilages and muscles, and carbohydrate metabolism, proteins and lipids, activating the sexual cycle events and the maturation of gonads. 20 Alteration in the frog metamorphosis rates was observed with homeopathically prepared thyroxine (Endler et al, 21 Welles et al 22 and Weber et al 23 ). Guedes et al 6 observed that the metamorphosis rates were significantly inhibited compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…3 In fish it is present in form of follicles associated to the ventral aorta, it plays an important role influencing the growing of bones, cartilages and muscles, and carbohydrate metabolism, proteins and lipids, activating the sexual cycle events and the maturation of gonads. 20 Alteration in the frog metamorphosis rates was observed with homeopathically prepared thyroxine (Endler et al, 21 Welles et al 22 and Weber et al 23 ). Guedes et al 6 observed that the metamorphosis rates were significantly inhibited compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of potentised T4 on Alpine frogs (Rana temporaria) metamorphosis has been a stable and well reproducible result since early 1990's, including repetitions in five different laboratories with a total N > 3,000 tadpoles. [41][42][43] Opposite to the effect of T4 in measurable doses, a high dilution of T4 slowed down metamorphosis. Similar results were obtained by Guedes and co-workers in Brazil, it means, in different climatic conditions and using a different species of frog (Rana catesbeiana).…”
Section: Conceptual Aspectsmentioning
confidence: 99%
“…Still regarding to external influences, a recent pilot study suggests the blocking effect of certain magnetic fields, such as microwave oven and cell phone derived fields on homeopathic preparations of T4. 43 The specificity of T4 has not yet been verified, by using as control, instead of T4, another similar molecule without physiological action.…”
Section: Conceptual Aspectsmentioning
confidence: 99%
“…Upon observation, the researchers reported that frogs treated with 10 30 potency of thyroxine jumped less and were significantly less active than the group treated with pure water. a follow-up study applied thyroxine at 10 30 potency and observed the metamorphosis rates of Rana temporani tadpoles (Weber, et al, 2008). they reported the tadpoles treated with test solutions developed 5 to 10% slower than control animals.…”
Section: Serial Dilution Effect Applied To Animal Behaviormentioning
confidence: 99%